Effect of tomato genotypes with varying levels of susceptibility to Tetranychus evansi on performance and predation capacity of Phytoseiulus longipes - Savi, Patrice Jacob [UNESP]; Moraes, Gilberto Jose de; Andrade, Daniel Junior de [UNESP] (Springer, 2021)
Tetranychus evansi Baker & Pritchard (Acari: Tetranychidae) is an invasive tomato pest in several African, American, Asian and European countries, with potential to reduce yield by up to 90%. Populations of the predaceous phytoseiid mite Phytoseiulus longipes Evans (Acari: Phytoseiidae) has been reported to have high potential for controlling T. evansi. However, tomato genotypes can potentially affect the performance of T. evansi and the predation ability of P. longipes. We evaluated the performance and predation capacity of P. longipes feeding on T. evansi nymphs on the two cultivated genotypes widely grown in Western Africa and a breeding genotype. The two commercial evaluated genotypes were Tounvi (susceptible, with few trichomes), TLCV15 (susceptible, with many trichomes), and the breeding genotype was SPJ-05-2018 (partially resistant with many glandular trichomes) selected from interspecific crossing TLCV15 and PI 13447 (highly resistant wild tomato genotype). We hypothesized that the susceptible genotype (with fewer trichomes) would be more favorable for P. longipes when compared to the susceptible or partially resistant genotypes (with a higher numbers of non-glandular or glandular trichomes). Intrinsic rate of increase (r) and predation potential (omega) of P. longipes were significantly reduced on SPJ-05-2018, possibly due to a negative effect of its glandular trichomes. Although the intrinsic rate of increase was higher on both susceptible genotypes (TLCV15 and Tounvi), predation potential was higher on TLCV15. Our results refuted the hypothesis that T. evansi-susceptible genotype with fewer trichomes would be more favorable to P. longipes.
Keywords: Two-sex life table; Population; Predation potential; Phytoseiid mite; Trichomes